Предмет: Математика,
автор: MrLexeon135
(0,2x-1)²=
(3x-2)²=
(6pg²-pg³)²=
6y-(y-2)²=
(2a-3b)²-2a(a+4)=
Допоможіть срочно!!!!
Ответы
Автор ответа:
0
(0,2x-1)²=0.04х²-0.4х+1
(3x-2)²=9х²-12х+4
(6pg²-pg³)²=36р²g^4-12p²g^5+p²g^6
6y-(y-2)²=6y-y²+4y-4=10y-y²-4
(2a-3b)²-2a(a+4)=4a²-12ab+9b²-2a²-8a=2a²-12ab+9b²-8a
(3x-2)²=9х²-12х+4
(6pg²-pg³)²=36р²g^4-12p²g^5+p²g^6
6y-(y-2)²=6y-y²+4y-4=10y-y²-4
(2a-3b)²-2a(a+4)=4a²-12ab+9b²-2a²-8a=2a²-12ab+9b²-8a
Автор ответа:
0
А що означає ^
Похожие вопросы
Предмет: Физика,
автор: noname67ioi
Предмет: Русский язык,
автор: prostatinae
Предмет: Математика,
автор: demanenkosveta928
Предмет: История,
автор: Аноним